KAJIAN YURIDIS TERHADAP PRAKTEK JUAL RUGI DALAM PERSAINGAN USAHA DI INDONESIA DAN DI MASYARAKAT UNI EROPA: Juridical Review Of Selling Practice at A Loss in Business Competition in Indonesia and in The European Union Community - Nitriko Puji Raharjo; Dhany Rahmawan (Faculty of Law, Universitas Trisakti, 2024)
The rule sale of goods at a price lower than their cost in Indonesia is outlined in Article 20 of Law Number 5 of 1999, which specifically addresses the Prohibition of Monopolistic Practices and Unfair Business Competition. Similarly, the European Union tackles this practice in Article 102 of the Treaty on the Functioning of the European Union (TFEU). The study used a normative legal methodology, descriptive research and relying mostly on secondary sources for information qualitative analysis and deductive reasoning to get conclusions. The result and Conclusion, this study showcases the enforcement of regulations against selling products below cost in Indonesia, particularly via the implementation of Article 20 of Law Number 5 of 1999. In Indonesia, the settlement of the problem of selling at a loss is supervised by the Business Competition Supervisory Commission (KPPU), whereas the European Union addresses it via the European Commission (EC) in compliance with the applicable selling legislation. Deficit Article 102 refers to a distinct segment or clause inside a text or legal structure. The Treaty on the Functioning of the European Union (TFEU) is a legal agreement that outlines the operational principles and rules of the European Union.